Discontinuities in the age-victimization profile and the determinants of victimization - Anna Bindler; Randi Hjalmarsson; Nadine Ketel; Andreea Mitrut (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
Many rights are conferred on Dutch youth at ages 16 and 18. Using national register data for all reported victimizations, we find sharp and discontinuous increases in victimization rates at these ages: about 13% for both genders at 16 and 9% (15%) for males (females) at 18. These results are comparable across subsamples (based on socio-economic and neighborhood characteristics) with different baseline victimization risks. We assess potential mechanisms using data on offense location, cross-cohort variation in the minimum legal drinking age driven by a 2014 reform, and survey data of alcohol/drug consumption and mobility behaviors. We conclude that the bundle of access to weak alcohol, bars/clubs and smoking increases victimization at 16 and that age 18 rights (hard alcohol, marijuana coffee shops) exacerbate this risk; vehicle access does not play an important role. Finally, we do not find systematic spillover effects onto individuals who have not yet received these rights.
Keywords: K42; K36; J13; I12; I14; 330; victimization; crime; youth; youth protection laws; alcohol; inequality; RDD